An exploration of the uptake of asymptomatic COVID-19 lateral flow testing in Birmingham, UK: cross-sectional survey and qualitative analysis. (November 2021) - Mathers, Jonathan; Poyner, Christopher; Thompson, Dean; Rudge, Gavin; Pritchett, Ruth
Abstract: Background: Rapid COVID-19 lateral flow testing is being offered at a population level in the UK to screen for asymptomatic infection. This public health policy is dependent on population uptake. Our research aimed to provide preliminary data to explore the experiences and opinions of residents in Birmingham, UK, of lateral flow testing. Methods: An online survey available to Birmingham residents was advertised online, via social media and COVID-19 testing centre adverts. It investigated reasons for and against testing, patterns of testing, experiences of testing, views regarding test accuracy, and post-test behaviours. Semistructured interviews with a purposive sample (n=21) of survey respondents explored participants' views in depth. We undertook descriptive statistics and rapid qualitative analysis (NVivo 11). Ethical approval was granted by the University of Birmingham and all participants provided informed consent. Findings: The survey opened on April 9, 2021, and closed May 19, 2021, and 220 people took part. Respondents were of mean age 45 years (SD 15·4) and 68% (n=150) were female, 22% (n=48) were male, 6% (n=13) did not choose a category, 3% (n=6) preferred not to say, and 1% (n=3) were non-binary. 87% (n=191) identified as White British, Irish, or other, 4% (n=8) did not choose a category, 3% (n=6) were Asian, Asian British, Indian, Pakistani, Bangladeshi, or other, 2% (n=5) were mixed race or other, 2% (n=5) preferred not to say, 2% (n=4) were Black, Black British, Caribbean, African, or other, and less than 1% (n=1) reported other. Respondents reported variable uptake and patterns of testing at one or more settings; 65% (n=144) reported testing twice weekly in line with government advice, 20% (n=45) more flexibly, often before social contacts, and 21% (n=47) had not tested yet. Within households with school children, patterns of testing varied considerably. Reasons given for not testing included beliefs about being at low personal risk of infection, stated adherence to government guidelines on physical distancing, and having received a vaccination. Some respondents were concerned about the implications of self-isolation after a positive result. Other barriers included time, availability of sufficient tests for larger families, the test reporting system, and physical discomfort. Concerns over lateral flow testing accuracy were common and dissuaded some from testing; however, a negative test still often provided peace of mind before engaging in social interactions. Interpretation: Although not a representative sample, these are the first in-depth findings indicating varied and flexible approaches to asymptomatic testing, some outside of contemporaneous current guidance. Approaches are influenced by personal perceptions of risk and test accuracy, test availability, reporting systems, and, to a lesser extent, perceived consequences of a positive result. School testing advice might not be consistently adhered to nationally. Despite accuracy concerns, respondents stated that negative test results often sanctioned social interaction. Funding: None.